2013
DOI: 10.2214/ajr.12.9657
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lymphovascular Invasion in Rectal Cancer by Preoperative CT

Abstract: Patients having rectal cancers with LVI showed a significantly increased mean superior hemorrhoidal vein diameter at presentation, which could be identified with pretreatment CT and help to direct the application of neoadjuvant treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
2
24
1
Order By: Relevance
“…Another limitation is related to the relatively low number of patients with metastatic disease at baseline. Although Wu et al showed that the cases with metastases in their cohort had significantly higher IMV diameter than those without metastases [5], we did not observe a similar statistical difference in our study but this is likely to be related to the small number of those with metastases in our cohort (9/80). We also based the evidence of EMVI on MRI findings alone, with no histological correlation, as all patients underwent CRT before consideration of surgical resection.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Another limitation is related to the relatively low number of patients with metastatic disease at baseline. Although Wu et al showed that the cases with metastases in their cohort had significantly higher IMV diameter than those without metastases [5], we did not observe a similar statistical difference in our study but this is likely to be related to the small number of those with metastases in our cohort (9/80). We also based the evidence of EMVI on MRI findings alone, with no histological correlation, as all patients underwent CRT before consideration of surgical resection.…”
Section: Discussioncontrasting
confidence: 95%
“…This significant difference persisted when replicating the measurements in correlation with the mrTRG ( P = 0.0001), LN involvement ( P = 0.0001) and the EMVI ( P = 0.0001). Previous studies have shown that colorectal cancer is associated with increased splanchnic venous diameter as a marker of EMVI and can potentially add value to prognostication . Three possible mechanisms for the correlation between the splanchnic venous return and tumoural invasion have been described: (i) increased venous drainage due to tumoural hypervascularity, (ii) arterialization of the splanchnic veins due to arteriovenous shunts and (iii) increased venous pressure secondary to tumoural thrombosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the measurement of the IMV ex vivo may not correlate with the measurement on CT because of lack of circulation, flow and venous pressure and potential changes in vessel elasticity ex vivo. As we state in the paper, and Akingboye et al also state, the hypothesis is that change in vessel diameter is probably partly because of changes in splanchnic circulation and venous return secondary to tumorigenesis [5]. Also, a recent study has shown that portal vein diameter measured on CT in healthy individuals does not correlate well with 'normal' quoted reference values, the vessel being larger [6].…”
mentioning
confidence: 70%